Disrupting AGR2/IGF1 paracrine and reciprocal signaling for pancreatic cancer therapy - Li, Hongzhen; Zhang, Zhiheng; Shi, Zhao; Zhou, Siqi; Nie, Shuang; Yu, Yuanyuan; Zhang, Lingling; Sun, Yifeng; Fang, Chao; Hu, Jingxiong; Niu, Yiqi; Schuck, Kathleen; et al. (Cell reports. Medicine, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is highly aggressive and characterized by pronounced desmoplasia. PDAC cells communicate with cancer-associated fibroblasts (CAFs) in a paracrine/reciprocal manner, substantially promoting tumor growth and desmoplastic responses. This study highlights the critical role of anterior gradient 2 (AGR2), an endoplasmic reticulum protein disulfide isomerase, secreted by PDAC cells to activate CAFs via the Wnt signaling pathway. Activated CAFs, in turn, secrete insulin-like growth factor 1 (IGF1), which enhances AGR2 expression and secretion in PDAC cells through the IGF1 receptor (IGF1R)/c-JUN axis. Within PDAC cells, AGR2 acts as a thioredoxin, aiding the folding and cell surface presentation of IGF1R, essential for PDAC’s response to CAF-derived IGF1. This reciprocal AGR2/IGF1 signaling loop intensifies desmoplasia, immunosuppression, and tumorigenesis, creating a harmful feedback loop. Targeting both pathways disrupts this interaction, reduces desmoplasia, and restores anti-tumor immunity in preclinical models, offering a promising therapeutic strategy against PDAC.